Acceptance of Artificial Intelligence in Advertising Agencies - Grzegorz LESZCZYNSKI; Karolina SALAMON; Marek ZIELINSKI (Communications of International Proceedings, 2021)
As the entities acting in a dynamic environment, advertising agencies constantly need to adapt to growing market requirements by improving their services, shortening service time, and reducing costs. The tools that might contribute to the growth of operational efficiency and the quality of the agency output are the solutions based on Artificial Intelligence. This paper aims to explore the factors influencing the acceptance of Artificial Intelligence in the work of an advertising agency. The exploratory, qualitative research was conducted among purposively chosen advertising agencies' managers. The obtained results allowed identification of their attitude towards the use of AI and their approach to substituting human labor with AI, and the consequences of AI for advertising agencies' performance.
Keywords: Artificial Intelligence; advertising agencies; management; change; innovation acceptance